A business value oriented approach to decision support systems. (10th June 2016) - Carton, Fergal; Hynes, Tim; Adam, Frederic
Abstract: With an increased emphasis on cost reduction and device agnosticism, Chief Information Officers (CIOs) increasingly struggle to justify investments in technology, typically lacking a vision linking those investments (in applications, infrastructure or integration) with value to business decision makers. Without guidance from a proper model of custodianship for enterprise wide master data, both structured and unstructured, exploring and exploiting value from the information assets of the enterprise becomes problematic. This paper uses a case study on management decision-making in a corporate environment to illustrate the fragmentation of enterprise data models, and argues for a different approach to understanding the value of data in organisations, where enterprise data assets are conceptualised in their entirety rather than from within application silos. It is proposed that data access should be governed in a centralised and secure manner, such that decision support applications consuming that data can be created quickly and economically. In this scenario, CIO attention is re-dispositioned from infrastructure maintenance to business decision value.